Congenital hypothyroidism screening with umbilical cord blood thyroid-stimulating hormone at birth and peripheral venous blood thyroid-stimulating hormone after 72 h at a hospital in suburban area of Chhattisgarh - Bhalendu Pratap Singh; Naresh P Motwani; C Sudhakar; Uma Chaturvedi (Indian Journal of Child Health, 2021)
Background: Primary congenital hypothyroidism (CH) is the most common cause of hypothyroidism in infancy and early childhood. Neonatal screening programs for the detection of CH in the neonatal period are widespread and in most screening programs, blood samples are collected at 5–6 days age. Objective: The objective of the study was to obtain cord blood (CB) samples at birth and the peripheral venous blood sample of thyroid-stimulating hormone (TSH) at 72 h. Materials and Methods: This cross-sectional observational study was done at a tertiary suburban center and a total of 1470 newborn delivered was enrolled after satisfying the inclusion criteria. Umbilical CB TSH sample was taken at birth and peripheral venous sample for TSH was taken at 72 h. TSH values more than 20 ?IU/mL, in both groups, were taken as an upper limit of normal. Results: Out of 1470 samples collected, among those with umbilical cord sample, 31 (2%) had a value >20 ?IU/mL, while only one baby had a value of TSH >20 ?IU/mL at 72 h of life and was diagnosed as CH. Conclusion: The incidence of CH is 1 out of 1470 neonates. Female gender, maternal age, and lower socioeconomic status of parents have a significant impact on umbilical cord TSH Levels.